Pengembangan Kewirausahaan Digital di Indonesia - Nurul Aini; Dian Martha Nurrul Amanah; Novinda Krisna Putri (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2023)
P The potential for the digital economy in Indonesia is enormous and is predicted to continue to grow. Indonesia is a very strategic market for digital products and services. The effect of using technology also influences the individual's desire to start a business. This research will examine how the concept of developing digital entrepreneurship in Indonesia uses the basic theory that is generally used in the field of government, namely the theory of policy actors. This study aims to provide a comprehensive analysis of the development of digital entrepreneurship in the digital economy era in Indonesia. The benefits of this research are expected to contribute to the discovery of digital entrepreneurship development in Indonesia. This research is an explorative qualitative research based on literature and literature study. Data analysis techniques are carried out by analyzing the contents of the data that has been collected. Based on the analysis that has been carried out, the development of digital entrepreneurship in Indonesia has been carried out using the pentahelix approach model which has involved 5 stakeholders namely government, business, academia, community and mass media. Each stakeholder has been well realized and synergizes with each other. The development of digital entrepreneurship must continue to be carried out with the development of access to internet technology and digitally literate human resources.